Exploring QGP signature in small system: Insights from ALICE in p–Pb and pp collisions - Patra Rajendra Nath (EPJ Web of Conferences)
The formation of quark-gluon plasma (QGP) has been confirmed in ultra-relativistic heavy-ion (i.e. Pb-Pb) collisions. Results from small collision systems, such as proton-ion (p–Pb) and proton-proton (pp) collisions at LHC energies, have revealed several notable features: a hardening of the pT-spectra and evidence of radial flow, an enhancement in (multi-)strange hadron production with increasing multiplicity, and non-zero anisotropic flow coefficients. These observations suggest the presence of collective effects, similar to those found in the QGP in heavy-ion collisions. In the searching of QGP formation in small collision systems, in particular, high-multiplicity (HM) p–Pb and pp collisions are essential as their charged-particle multiplicity is comparable to that of peripheral heavy-ion collisions. This proceeding presents the LHC Run 2 results of light-flavour hadron (π, K, p) production in high-multiplicity pp collisions at √s = 13 TeV with a focus on transverse momenta (pT) spectra, mean transverse momenta (〈pT〉), ratio of pT-spectra and the ratio of the integrated yields of kaon-to-pion and proton-to-pion. The results are compared with that of heavy-ion collisions. The anisotropic flow (v2) measurement in high-multiplicity p–Pb collisions at √sNN = 5.02 TeV and pp collisions at √s = 13 TeV are also shown and compared with the results from Pb–Pb collisions.